Pseudoradial Nerve Palsy Caused by Acute Ischemic Stroke - Hassan Tahir MD; Vistasp Daruwalla MD; Jeremy Meisel MD; Samir E. Kodsi MD (SAGE Publishing, 2016)
Pseudoperipheral palsy has been used to characterize isolated monoparesis secondary to stroke. Isolated hand nerve palsy is a rare presentation for acute cerebral stroke. Our patient presented with clinical features of typical peripheral radial nerve palsy and a normal computed tomography scan of the head, which, without a detailed history and neurological examination, could have been easily misdiagnosed as a peripheral nerve lesion deferring further investigation for a stroke. We stress the importance of including cerebral infarction as a critical differential diagnosis in patients presenting with sensory-motor deficit in an isolated peripheral nerve pattern. A good history and physical exam can differentiate stroke from peripheral neuropathy as the cause of radial nerve palsy.